Acid-induced intermolecular [3+2] cycloaddition/oxidation to synthesize polysubstituted benzo[f]isoindole-4, 9-diones. Issue 9 (September 2019) - Lin, Zhang-qi; Li, Chao-dong; Li, Yu-jin; Zhang, Yong-jian; Zhou, Zi-chun; Ye, Qing; Gao, Jian-rong
A novel one-pot 1, 3-dipolar cycloaddition/oxidation reaction of 1, 4-quinones, aromatic aldehydes, and N -substituted amino esters to construct polysubstituted benzo[ f ]isoindole-4, 9-diones induced by benzoic acid is reported. Based on optimized reaction conditions, various polysubstituted benzo[ f ]isoindole-4, 9-diones derivatives are obtained in moderate yields. This straightforward methodology employs mild reaction conditions, a green oxidant, and readily available starting materials. Notably, a wide range of substrates is tolerated.